The impact of COVID-19 on residential rehabilitation programs for individuals with substance use disorder - Hemasinghe, Imesha H. N.; Jayamaha, Akila R.; Herath, Nimesha D. M.; Ranadeva, Nadeeka D. K.; Dharmarathna, Nishadi D.; Senanayake, Bhadrani; Thamara Darshana; Renuka, Nilani; Samarasinghe, Kerstin L.; Fernando, Neluka (International Journal Of Community Medicine And Public Health, 2023)
According to UNODC and WHO global estimates, only one in six individuals with substance use disorder (SUD) has access to residential rehabilitation programmes. This proportion further declined as a result of COVID-19 pandemic, which caused devastating problems to the individuals with SUD. The provision of residential treatment for individuals with SUD was interrupted due to COVID-19, in the aspects of the rehabilitation program, recruitment and service provision for rehabilitees or clients, staff and the infrastructural facilities. Further, individuals with SUD are known to have a greater risk of being infected with COVID-19 virus and developing post COVID complications due to their unstable psychological state, weakened immunity, malnutrition and other health related complications which have arisen with the prolonged use of substances. There is a timely need to provide a substantial emphasis on individuals with SUD during COVID-19 pandemic and to undertake the necessary steps to deliver the needed treatment. Critical appraisal of the available empirical evidence is instrumental prior to the laying-out and providing residential rehabilitation amidst the COVID-19 pandemic. Hence, the current review intended to explore the impact of the COVID-19 pandemic on residential rehabilitation for individuals with SUD by scrutinizing the latest empirical evidence in order to battle against the future pandemic situations.